1990
DOI: 10.1002/j.1460-2075.1990.tb07484.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of synthetic Holliday junctions in DNA by an endonuclease activity from calf thymus.

Abstract: Extracts of calf thymus have been fractionated to reveal a nuclease activity that specifically cleaves model Holliday junctions in vitro. The products of cleavage are unbranched linear duplex DNA molecules. Using synthetic four‐way junctions, we show that the major sites of cutting are diametrically opposed, at sites one nucleotide from the base of the junction. Other types of four‐way junctions, including pseudo‐cruciform structures and cruciforms extruded from supercoiled plasmids, are also cleaved by the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 43 publications
1
69
0
Order By: Relevance
“…The evidence for diagonal digestion of cruciform DNA suggested that the resolution activity for Hollidayjunction structures in mammalian cells 28 could participate in this reaction. MUS81 nuclease, GEN1 and a complex of SLX4-SLX1 have been proposed as candidates for such a resolvase in mammalian cells [29][30][31][32][33][34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…The evidence for diagonal digestion of cruciform DNA suggested that the resolution activity for Hollidayjunction structures in mammalian cells 28 could participate in this reaction. MUS81 nuclease, GEN1 and a complex of SLX4-SLX1 have been proposed as candidates for such a resolvase in mammalian cells [29][30][31][32][33][34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…Although eukaryotic Holliday junction resolvases have not yet been identified, related activities have been observed during the fractionation of mammalian extracts (Elborough and West 1990;Hyde et al 1994), indicating that similar junction-processing events are likely to occur in eukaryotes. Our data indicate that factors that affect the assembly of the resolvase at the site of the junction may affect the outcome of a recombination event.…”
Section: Discussionmentioning
confidence: 99%
“…Direct Association of RAD51C and XRCC3 with HJ Resolvase Activity-The resolvase activity present in HeLa and hamster cell extracts has also been detected in a variety of calf and rabbit organ tissues (thymus, testis, and spleen) (37)(38)(39). An identical activity is found in plant extracts, such as those obtained from wheat germ, giving us a unique opportunity to determine whether exogenous expression of RAD51C (effectively using an in vitro transcription/translation system) in a wheat germ extract stimulates or blocks the endogenous resolvase activity present in the extract.…”
Section: Interaction Of the Resolvase Complex With Holliday Junctions-mentioning
confidence: 99%